Perception by Laypersons and Healthcare Professionals Towards Oral and Maxillofacial Surgery (Bangladesh Journal of Medical Science, 2013)
Background: Oral and maxillofacial surgery (OMFS) is a surgical branch of dentistry that deals with the wide spectrum of diseases, injuries and defects in the maxillofacial region. There are plenty of people who have lack of awareness towards the wide surgical scope provided by OMFS as reported by previous study done in Boston in 1996. The purpose of this study was to assess the level of awareness among the general public and healthcare professionals towards Oral and Maxillofacial Surgery specialty in Hospital Universiti Sains Malaysia (HUSM). Materials and Methods: A total of 186 standardized questionnaire was distributed to 6 groups of respondents which include laypersons attending HUSM, 4th year dental and medical students, dental officers, medical officers and paramedical workers from various departments such as Emergency department, Ear, Nose and Throat (ENT) department, medical family clinic and dental clinic of HUSM. Results: The data showed that 100% of students and practitioners had heard of OMFS, whereas only 68.9% of the laypersons have heard of the specialty. Furthermore, only 11.6% of the lay responders had been treated by an OMFS. The full results also suggested that about 50% of laypersons, 35% of medical professionals and 30% of dental professionals had lack of understanding about the range of care provided by OMFS specialty. Conclusion: A thorough education need to be implemented among dental and medical undergraduate students as well as professionals so that they can make a proper referral later on and automatically provide correct information to the laypersons. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 199-208 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14950